2020
DOI: 10.15446/rfnam.v73n1.77735
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of the red dragon fruit - Selenicereus undatus (Haw.) D.R. Hunt – under growing conditions in the municipality of San Jerónimo (Antioquia, Colombia)

Abstract: The red dragon fruit Selenicereus undatus is a native fruit from the Americas. Its growing appeal in the international market as an exotic fruit highlights the relevance of the crop for the local economies. In Colombia, the high diversity within the genus and species makes it difficult to have reliable materials for propagation as cultivars. This agronomic challenge requires more studies of the distribution and real diversity within the genus Selenicereus sp. Due to the information aforementioned, the fruit is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
5
6
1
Order By: Relevance
“…Total soluble solids, being the most desirable character in view of consumers' preference, measured as °Brix, which can be affected by a set of factors such as genetic, climatic, soil, management, among others [27][28][29] . In the present study, the TSS ranged between 9.1 to 18.3 o B representing better fruit quality which evidenced by the earlier report that the TSS values between 11 to 15 o B have good market preference 30 .…”
Section: Discussionsupporting
confidence: 80%
“…Total soluble solids, being the most desirable character in view of consumers' preference, measured as °Brix, which can be affected by a set of factors such as genetic, climatic, soil, management, among others [27][28][29] . In the present study, the TSS ranged between 9.1 to 18.3 o B representing better fruit quality which evidenced by the earlier report that the TSS values between 11 to 15 o B have good market preference 30 .…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the genotypes showed the shape of margin between areolas between concave and right, contrary to that reported in other studies on different species of Hylocereus, where the predominant forms were convex, with the presence of wax [8]. The cladode width and distance between areoles corresponded well with earlier studies from México [23], India [8], Puerto Rico and Colombia [6,[18][19][20].…”
Section: Discussioncontrasting
confidence: 52%
“…The morphological characteristics of these genotypes have yet to be elucidated [19]. Colombia has developed vastly with the cultivation of several dragon fruit genotypes but the morphological characteristics and adaptation to different altitudes have not been clearly studied [18]. Morphological and agronomic characteristics can be used to measure genetic diversity in a particular individual population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations